PLAYRANK: An Interactive Web System for Accounting and Analysis of Player and Team Ratings (Uzbekistan Open Conference, 2025)
The article describes the end-to-end development and implementation of the PlayRank web project—an interactive system for managing player ratings, dynamic team formation, and tournament organization. The project aims to comprehensively automate the process of collecting and analyzing game results while providing intuitive real-time visualization of statistical data. The modular system architecture, the rationale for the selected technology stack (HTML5, CSS3, JavaScript, Chart.js), and the results of functional testing are presented in detail. Special attention is given to the design of an adaptive user interface with a neon aesthetic, the implementation of client-side logic, and local data storage mechanisms using LocalStorage. The practical significance of the project for educational processes and the development of e-sports infrastructure in universities is discussed, and directions for the platform’s further development are outlined.